2008
DOI: 10.1063/1.2955741
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure and energetics of V+-benzene half-sandwiches of different multiplicities: Comparative multireference and single-reference theoretical study

Abstract: Multireference [complete active space self-consistent field (CASSCF) and multiconfigurational quasidegenerate perturbation theory (MCQDPT)] and single-reference ab initio (Moller-Plesset second order perturbation theory (MP2) and coupled clusters with singles, doubles and noniterative triples [CCSD(T)]) and density functional theory (PBE and B3LYP) electronic structure calculations of V(C(6)H(6))(+) half-sandwich in the states of different multiplicities are described and compared. Detailed analyses of the geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 60 publications
4
17
0
Order By: Relevance
“…To account for quantum effects in the nanotube growth, ab initio calculations using DFT with the three-parameter Becke , gradient-corrected exchange functional in conjunction with the Lee−Yang−Parr correlation functional (B3LYP) were carried out using the Gaussian 03 software . The B3LYP functional has been widely used to describe similar interactions. In particular, Polestshuk et al reported a very detailed study of metal−benzene interactions involving a comparative analysis of the electronic structure and diabatic and adiabatic dissociation energies using a series of multiconfigurational methods such as multiconfigurational quasidegenerate perturbation theory (MCQDPT) and complete active space self-consistent field (CASSCF) among others, as well as a group of single-configuration methods including Moller−Plesset second-order perturbation theory (MP2) and two DFT methods: B3LYP and PBE. It was concluded that B3LYP offers the best representation among the single configuration methods, outperforming both MP2 and the PBE functional, and yielding dissociation energies close to those of the best multiconfigurational method.…”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…To account for quantum effects in the nanotube growth, ab initio calculations using DFT with the three-parameter Becke , gradient-corrected exchange functional in conjunction with the Lee−Yang−Parr correlation functional (B3LYP) were carried out using the Gaussian 03 software . The B3LYP functional has been widely used to describe similar interactions. In particular, Polestshuk et al reported a very detailed study of metal−benzene interactions involving a comparative analysis of the electronic structure and diabatic and adiabatic dissociation energies using a series of multiconfigurational methods such as multiconfigurational quasidegenerate perturbation theory (MCQDPT) and complete active space self-consistent field (CASSCF) among others, as well as a group of single-configuration methods including Moller−Plesset second-order perturbation theory (MP2) and two DFT methods: B3LYP and PBE. It was concluded that B3LYP offers the best representation among the single configuration methods, outperforming both MP2 and the PBE functional, and yielding dissociation energies close to those of the best multiconfigurational method.…”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…Spectroscopy studies have included tunable laser electronic photodissociation ,, and photoelectron spectroscopy. Perhaps the most informative data about structures and bonding come from infrared photodissociation studies of mass-selected ions. Free electron lasers (FELs) have generally been employed for resonance-enhanced multiphoton dissociation (REMPD) studies in the fingerprint region, whereas IR optical parametric oscillator (OPO) laser systems have investigated the C–H stretching region, , usually using the method of tagging with rare gas atoms. Computational work has complemented many of these spectroscopic studies. Unfortunately, the infrared spectrum of isolated benzene in the C–H stretching region is complicated by the occurrence of a Fermi triad in the vibrational structure . This feature and its response to metal cation binding are not handled with standard harmonic computational methods, limiting the insight that can be gained in this region.…”
Section: Introductionmentioning
confidence: 99%
“…The missing dynamical correlations move the minimum to significantly larger V + −Bz distance of ≈2.6 Å, which QMC optimization with CASSCF nodal hypersurfaces reduces back to 2.41 Å, almost identical to the QMC-optimized values with other nodal hypersurfaces and MCQDPT value. 29 CASSCF nodal hypersurfaces yield DMC geometry similar to that of MCQDPT. However, the QMC energies, irrespective of DFT nodal hypersurface used, result in V + −Bz binding energy significantly higher by 0.26 eV than those obtained with DFT nodal hypersurfaces; see the SI.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 83%
“…Electronic and Atomic Structure of VBz + and CoBz + . The VBz + cation has extensively been studied by Polestshuk and collaborators, 29 who found, using MCQDPT technique, that the system ground-state has a quintet spin multiplicity and spontaneously reduces its symmetry from C 6h ( 5 A 2 (d 3 s 1 ) state) to the so-called "up-side-down-boat-shaped" (UDBS) geometry of C 2v symmetry ( 5 B 2 (d 4 ) state), see Figure 2. Quintet spin multiplicity was also found by Bauschlicher et al 27 using MCPF method, who considered C 6v symmetry.…”
Section: Resultsmentioning
confidence: 99%